How Differences in Herbal Beverage Consumer Decisions Based on Demographic Factors? - Nurhidayah Layoo; Sutrisno K. Djawa; Wahyudin Rahman; Nurjanna Ladjin; Amilia Zainita Saini; Cahyaning Raheni; Sulasmi Anggo (Universitas Muhammadiyah Yogyakarta, 2024)
For a long time, people have been consuming homemade herbal drinks, which are processed traditionally. However, micro, small, medium, and large-scale businesses are now emerging in the production and marketing of ready-to-consume packaged herbal drinks. Research is needed on whether there are differences in consumer motivation in using homemade and industrial-made herbal beverages in terms of the factors of age, gender, education, occupation, and marital status of consumers, as well as how the simultaneous influence of these five variables on the motivation to consume herbal drinks. This study used a sample of 327 people whose data was collected through a digital questionnaire. Data were analyzed using Mann Whitney, Kruskal Wallis, and multiple linear regression. The results showed differences in consumer decisions based on age, education, occupation, and marital status in the choice of herbal drinks, but not gender differences. Most consumers chose the non-packaged type. Simultaneous testing, age, and occupation factors significantly affected consumer decisions, while gender, education, and marital status were not necessary. The results have implications for the segmentation strategy, targeting, and market positioning of the herbal beverage processing industry and the herbal beverage raw material supply industry, better market understanding, more targeted product development, more effective promotional interventions, increased public awareness of the benefits of herbal drinks, and government policy support for the herbal beverage industry.